Agil-idade: um framework de educação ágil para pessoas idosas - De Bortoli, Lis Ângela (2024)
This thesis focuses on the integration of Agile Culture with Educational Gerontology in the non-formal sphere, with the theory of Lifelong Learning (ALV) as a backdrop. Educational gerontology in the non-formal sphere comprises educational activities carried out outside the traditional school environment, aiming to develop skills, knowledge and attitudes in less structured contexts. The agile culture, originating from software development and extended to education, is known for its emphasis on satisfaction and motivation of those involved, adaptability to change and collaboration. The general objective was to propose the Agile-Age framework, based on agile culture for educational gerontology, in the non-formal sphere. The specific objectives include: a) defining the conceptual basis based on the references that support the LMA, discussions about agile culture, as well as its articulation with educational gerontology, in the non-formal sphere, b) defining through co-design the agile manifesto of non-formal education for elderly people that served as the basis for Agility-Idade. c) customize, apply and evaluate Agility-Age with a group of elderly people, d) identify the acceptance of Agil-Age and what were its main contributions to educational gerontology. To meet these objectives, an exploratory research approach was adopted, combining exploratory study and mixed analysis. Agil-Idade was conceived through bibliographical research, co-design and literature mapping. The evaluation was carried out with the participation of six elderly people over 14 weeks, using questionnaires and interviews as data collection instruments. Three scientific productions related to this work were produced. The article presented in chapter 3, "Agile culture in teaching: a viable possibility", whose objective was to discuss agile culture in teaching, based on a comparison of agile manifestos for education and research conducted with teachers in the area of ​​Technology Information, answered part of the specific objective a. The article in chapter 4 entitled "Agile manifesto of non-formal education for older adults - a co-design experience", published in the journal Educational Gerontology, which aimed to discuss the agile culture in education and present the agile manifesto for non-formal education formal training for elderly people, as well as its elaboration process, covers specific objective b and part of a. The article in chapter 5 "A framework to support educational gerontology based on agile culture", which aims to present Agile-Age, includes specific objectives c and d. The final results indicate that Agil-Idade promoted collaboration and communication, keeping participants engaged, satisfied and valued, in addition to allowing the sharing of experiences and life trajectories.